Le spectre communiste, un fantôme dans la maison européenne - Bertrand Vayssière (Les Cahiers de Framespa)
Trying to write a history of ideas based on the study of the confrontation between Europeanism and Communism may seem incongruous: if Communism claims to be an ideology, Europeanism appears on the other hand as a mere practical option aiming at the integration of a continent. However, before becoming a reality, European construction was based on specific values, among which was the confrontation with other ideas, particularly Communism. This article will show that thinking about Europe implies thinking about how to fight against Communism and its expansionist tendencies. Hence a dialectical relationship between these two mental constructions, if only because of their simultaneous emergence in political debates, which lead historian Tony Judt to say that "the opposite of Communism was not capitalism but Europe".